Smith-Purcell Radiation from Microbunched Beams Modulated after Passing the Undulators in FELs; Free Electron Laser, EL2015 - Sergeeva D. Yu. Darjya Yurjevna; Potylitsyn A. P. Alexander Petrovich; Tishchenko A. A. Aleksey Aleksandrovich; Strikhanov M. N. Mikhail Nikolaevich (2015, 2015)
Title screen